1988
DOI: 10.1203/00006450-198807000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Cell Calcium Levels of Normal and Cystic Fibrosis Nasal Epithelium

Abstract: ABSTRACT. To determine whether epithelial ion transport abnormalities in cystic fibrosis (CF) might reflect abnormal regulation of intracellular Caz+ levels, cytosolic free calcium (Caiz+) was measured using fura-2 or quin2 in suspensions of normal or CF nasal epithelial cells derived from primary cell culture. The basal Ca?+ level measured with fura-2 in CF nasal epithelia was 155 f 9 nM (n = 5), a value not significantly different from normal nasal epithelia (143 f 16 nM, n = 5). Total cell calcium was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…A23187 has been used as a calcium ionophore in a large number of studies of epithelial ion transport, although measurement of intracellular calcium has been hindered by the fluorescent nature of this compound. However, ionomycin produces very similar effects (Willumsen & Boucher, 1989) and has been shown to directly elevate intracellular calcium in human nasal epithelium (Murphy, Cheng, Yankaskas, Stutts & Boucher, 1988). No stimulation of cyclic AMP levels by A23187 was seen in our tissues.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…A23187 has been used as a calcium ionophore in a large number of studies of epithelial ion transport, although measurement of intracellular calcium has been hindered by the fluorescent nature of this compound. However, ionomycin produces very similar effects (Willumsen & Boucher, 1989) and has been shown to directly elevate intracellular calcium in human nasal epithelium (Murphy, Cheng, Yankaskas, Stutts & Boucher, 1988). No stimulation of cyclic AMP levels by A23187 was seen in our tissues.…”
Section: Discussionsupporting
confidence: 62%
“…However, ionomycin produces very similar effects (Willumsen & Boucher, 1989) and has been shown to directly elevate intracellular calcium in human nasal epithelium (Murphy, Cheng, Yankaskas, Stutts & Boucher, 1988). No stimulation of cyclic AMP levels by A23187 was seen in our tissues.…”
Section: Discussionmentioning
confidence: 67%
“…The relative effects of recording from spherical cells should be similar with these two cell types, as they are of similar dimensions, but specific differences in intracellular influences on Fura-2 cannot be ruled out. For this reason, although the basal [Ca2+]i measured in our study is of the same order of magnitude as that reported by others (Murphy, Cheng, Yankaskas, Stutts & Boucher, 1988), absolute values obtained could only be taken as best available estimates. However, the relative changes in calcium concentration (expressed as a percentage of baseline) would be unaffected by the lack of absolute calibration standards.…”
Section: Effect Of Calcium Ionophore On Intracellular Free Calciumsupporting
confidence: 57%
“…This effect of isoprenaline was not observed in CF cell cultures pre-treated with amiloride. The failure of isoprenaline to increase apical membrane Clconductance 4-2 99 R. C. BOUCHER AND OTHERS does not result from an absence of adrenergic receptors, since isoprenaline stimulates cyclic AMP production equally well in CF and normal cultured nasal epithelial cells (Welsh & Liedtke, 1986;Murphy, Yankaskas, Stutts & Boucher, 1988).…”
Section: Pharmacological Agents/ion Substitutionmentioning
confidence: 99%